Classification of Derivational and Inflectional Morphemes in song lyric of Ariana Grande’s album Thank U, Next. - Euis Meinawati; Tisha Amanda Putri; Danang Dwi Harmoko; Herlin Widasiwi Setianingrum; Sufi Alawiyah (VELES Voices of English Language Education Society, 2020)
Morphology is the study of word and sub-discipline of linguistics that study of word, structure and form which has component such as morpheme, base, prefix and suffix. This process can reduce ambiguity during the process of correcting the words in sentences. This study investigated about the classification of derivational and inflectional morphemes in the song lyrics of Ariana Grande’s album Thank U, Next. The method in this research use descriptive qualitative method.Process of collecting data used to identify lyric that has derivational and inflectional morpheme. The result of this research is to indicate that the words recorded in song lyrics can be further analyzed about the process of forming words by words and the meaning of the word in it have different meaning from the literal meaning